Reducing the length of hospital stay after total knee arthroplasty: influence of femoral and sciatic nerve block - Carvalho Júnior,Lúcio Honório de (2015)
Objective: the aim of this study is to evaluate the change in length of hospital stay postoperatively for Total Knee Arthroplasty after using femoral and sciatic nerve block. Materials and methods: the medical records of 287 patients were evaluated, taking into account the number of hours of admission, the percentage and the reason for re-hospitalization within 30 days, as well as associated complications. All patients were divided into two groups according or not to whether they were admitted to ICU or not. During the years 2009 and 2010, isolated spinal anesthesia was the method used in the procedure. From 2011 on, femoral and sciatic nerve blocking was introduced. Results: between the years 2009 and 2012, the average length of stay ranged from 74 hours in 2009 to 75.2 hours in 2010. The average length of stay in 2011 was 56.52 hours and 53.72 hours in 2012, all in the group of patients who did not remain in the ICU postoperatively. In the same period, among those in the group that needed ICU admission, the average length of stay was 138.7 hours in 2009, 90.25 hours in 2010, 79.8 hours in 2011, and 52.91 hours in 2012. During 2009 and 2010, the rate of re-hospitalization was 0%, while in 2011 and 2012, were 3.44% and 1%, respectively. Conclusion: according to this study, the use of femoral and sciatic nerve blocking after total knee arthroplasty allowed significant reduction in hospital stay.